Molecularly Imprinted Titanium Dioxide: Synthesis Strategies and Applications in Photocatalytic Degradation of Antibiotics from Marine Wastewater: A Review - Han, Xue; Jin, Yu; Zhao, Luyang; Zhang, Yuying; Ren, Binqiao; Song, Xiaoxiao; Liu, Rui (Materials, 2025)
Antibiotic residues in the marine environment pose a serious threat to ecosystems and human health, and there is an urgent need to develop efficient and selective pollution control technologies. Molecular imprinting technology (MIT) provides a new idea for antibiotic pollution control with its specific recognition and targeted removal ability. However, traditional titanium dioxide (TiO2) photocatalysts have limited degradation efficiency and lack of selectivity for low concentrations of antibiotics. This paper reviews the preparation strategy and modification means of molecularly imprinted TiO2 (MI-TiO2) and its composites and systematically explores its application mechanism and performance advantages in marine antibiotic wastewater treatment. It was shown that MI-TiO2 significantly enhanced the selective degradation efficiency of antibiotics such as tetracyclines and sulfonamides through the enrichment of target pollutants by specifically imprinted cavities, combined with the efficient generation of photocatalytic reactive oxygen species (ROS). In addition, emerging technologies such as magnetic/electric field-assisted catalysis and photothermal synergistic effect further optimized the recoverability and stability of the catalysts. This paper provides theoretical support for the practical application of MI-TiO2 in complex marine pollution systems and looks forward to its future development in the field of environmental remediation.